DECISION SUPPORT SYSTEM FOR DETERMINING THE BEST OIL PALM SEEDS USING THE ANALYTICAL HIERARCHY PROCESS METHOD - Dedi Yunizar; Ahmad Syarifuddin; Kanti Lestari (International Journal of Artificial Intelligence and Robotic Technology, 2021)
The need for the availability of quality oil palm seeds with an increasing quantity is in line with the increasing need of the world's population for palm oil. Good care of seedlings in early nurseries and main nurseries through the right dose of fertilization is one of the efforts to achieve optimal results in the development of oil palm cultivation. Most villagers do not know and can choose and distinguish good types of oil palm seeds, due to lack of knowledge about the types of oil palm seeds. With this method, it will make it easier for ordinary people to choose superior types of oil palm seeds through predetermined criteria and subcriteria. To help and make it easier for the community to choose superior types of oil palm seeds, as well as to increase people's insight into the types of superior seeds of oil palm.